Rats’ umbilical-cord mesenchymal stem cells ameliorate mast cells and Hsp70 on ovalbumin-induced allergic rhinitis rats - Lia Restimulia; Syafruddin Ilyas; Delfitri Munir; Agung Putra; Teti Madiadipoera; Farhat Farhat; Rosita Juwita Sembiring; Muhammad Ichwan; Nur Dina Amalina (Medicinski glasnik, 2022)
Aim: Allergic rhinitis (AR) is a heterogeneous condition that has been associated with inflammatory responses and is characterized by clinical typical symptoms of nasal itching, sneezing, watery discharge and congestion. Mesenchymal stem cells (MSCs) are multipotent stem cells that have the immunoregulatory ability by secreting various cytokines which potent as a promising therapeutic modality for allergic airway diseases, including AR. The aim of this study was to investigate the effect of rat UC-MSCs on the number of mast cells, the expression of Hsp70 indicated by the nasal symptoms allergic, particularly nasal rubbing in ovalbumininduced AR rats. Methods: Fifteen male Wistar rats (6 to 8 weeks old) were randomly divided into three groups (control group, sham group, and OVA+MSCs group). OVA nasal challenge was conducted daily from day 15 to 21, and UC-MSCs (1x106 ) were administrated intraperitoneally to OVA-sensitized rats on day 21. Nasal rubbing was observed from day 22 to 28. The rats were sacrificed on day 22 and day 28. The nasal cavity tissues were prepared for histological observations. Results: The administration of UC-MSCs could reduce the number of mast cells and the expression of Hsp70 leading to reduction of nasal symptoms allergic, particularly nasal rubbing. Conclusion: Based on this finding, MSCs present a promising immediate curative effect to the inflammatory reaction in AR rats.
Keywords: allergic rhinitis; Hsp70; mast cells; MSCs; ovalbumin